Ninth International Conference on Information Visualisation (IV'05)
DOI: 10.1109/iv.2005.122
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Animated Transitions on User Navigation in 3D Tree-Maps

Abstract: This paper describes a user study conducted to evaluate the use of smooth animated transitions between directories in a three-dimensional, tree-map visualization. We looked specifically at the task of returning to a previously visited directory after either an animated or instantaneous return to the root location. The results of the study show that animation is a double-edged sword. Even though users take more shortcuts, they also make more severe navigational errors. It seems as though the promise of a more d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 18 publications
(25 reference statements)
1
21
0
1
Order By: Relevance
“…One-second animations worked as well as three-second ones. This is in agreement with the menu transitions study of Bladh et al [2].…”
Section: Duration and Amountsupporting
confidence: 93%
See 1 more Smart Citation
“…One-second animations worked as well as three-second ones. This is in agreement with the menu transitions study of Bladh et al [2].…”
Section: Duration and Amountsupporting
confidence: 93%
“…In the research by Bladh et al it has been found that short animations during navigation with 3D maps affect user performance and reduce task times when e.g. counting details on maps [2]. Klein & Bederson measured better results in reading when scrolling animation was used [3].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional slice-and-dice approach [1] has been enhanced by squarified [5], ordered [5], Voronoi [6], or generalized layouts [4]. There are also radial layouts [7] and different three-dimensional approaches [8]. Cascaded treemaps [9] have been developed to emphasize containment within tree structure, but at the cost of space.…”
Section: The Treemap Display and Related Workmentioning
confidence: 99%
“…Extensions of Treemap for visualization in 3-dimensional space have been considered by Rekimoto and Green [25], Bladh et al [9], and Bladh et al [8]. A variant of Treemap that constructs radial partitions was proposed by Stasko et al [29].…”
Section: Related Workmentioning
confidence: 99%